SEJARAH PERKEMBANGAN BAHASA JEPANG DAN PENELITIANNYA - Nani Sunarni; Onin Najmudin (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2018)
There is a long history of the development and research of Japanese language. Morita (1990:282) divided the development of Japanese language into seven periods: Kodai (13000BC–600AD), Jodai (600-784), Chuuko (784- 1184), Chuusei (1184-1603), Kinsei (1603-1867),Kindai (1868-1945), and Gendai (1946-1989). On the other hand, Hibatani (1996) indicatedfive periods of Japanese language development: Nara (710) Jouko Nihongo’Old Japanese’,Heian (794) Chuuko Nihongo’ Late Old Japanese’, Kamakura (1185/1192), Muromachi[1331/1392] ) Chuusei Nihongo’Middle Japanese’, Edo (1603) Kinsei Nihongo’ or EarlyModern Japanese’, and Meiji (1868), Taisho (1912), Showa (1926), Heisei (1989) - GendaiNihongo as ’Modern Japanese’. The present study aims to identify the development as well asstudies of Japanese language from old to modern period. Thus, the present study aims todiscuss the birth of Japanese language from the adoption of the Chinese language of kanbunand kanji by the Buddhist monks, the research of writings from Nara period in which thereading of Japanese language was started, bushu ‘radical’, sound, as well as the meaning ofKanji and the research toward koten-kogo that delivered the change in phoneme, joshi(kantou joshi), and prefix. In addition, there is a discussion toward the birth of waka danrenga lahir te, ni o, ha in Kanazukai’s study which became a milestone for grammar andphoneme change.